Bibliometric Analysis of Trends and Patterns in Sustainable and Responsible Investments (SRI) Research from 2000-2024 - Judijanto, Loso; Ladjin, Nurjanna; Harsono, Iwan; Amalia , Mekar Meilisa; Sangaji, Joko (Westscience Press, 2024)
This study provides a comprehensive bibliometric analysis of Sustainable and Responsible Investments (SRI) research from 2000 to 2024, utilizing data visualization tools to map the evolution and current state of the field. Through thematic clusterization, temporal trends, author collaboration networks, and potential research topics, the research offers insights into the dynamic nature of SRI. Initial findings show a progression from foundational concepts to more nuanced discussions around impact investing and sustainability indices. The analysis of author collaboration networks highlights key influencers and suggests potential areas for future collaboration. Additionally, the identification of underexplored areas such as ethical investment frameworks and the impact of social investments indicates new directions for research. This paper underscores the importance of SRI in aligning financial investments with global sustainability goals, providing a roadmap for future research and practice in the field.